NNMT‐DNMT1 Axis is Essential for Maintaining Cancer Cell Sensitivity to Oxidative Phosphorylation Inhibition - Changqing Wu; Yu'e Liu; Wenju Liu; Tianhui Zou; Shaojuan Lu; Chengjie Zhu; Le He; Jie Chen; Lan Fang; Lin Zou; Ping Wang; Lihong Fan; et al. (Advanced Science, 2023)
Abstract Lacking a clear understanding of the molecular mechanism determining cancer cell sensitivity to oxidative phosphorylation (OXPHOS) inhibition limits the development of OXPHOS‐targeting cancer treatment. Here, cancer cell lines sensitive or resistant to OXPHOS inhibition are identified by screening. OXPHOS inhibition‐sensitive cancer cells possess increased OXPHOS activity and silenced nicotinamide N‐methyltransferase (NNMT) expression. NNMT expression negatively correlates with OXPHOS inhibition sensitivity and functionally downregulates the intracellular levels of S‐adenosyl methionine (SAM). Expression of DNA methyltransferase 1 (DNMT1), a SAM consumer, positively correlates with OXPHOS inhibition sensitivity. NNMT overexpression and DNMT1 inhibition render OXPHOS inhibition‐sensitive cancer cells resistant. Importantly, treatments of OXPHOS inhibitors (Gboxin and Berberine) hamper the growth of mouse tumor xenografts by OXPHOS inhibition sensitive but not resistant cancer cells. What's more, the retrospective study of 62 tumor samples from a clinical trial demonstrates that administration of Berberine reduces the tumor recurrence rate of NNMTlow/DNMT1high but not NNMThigh/DNMT1low colorectal adenomas (CRAs). These results thus reveal a critical role of the NNMT‐DNMT1 axis in determining cancer cell reliance on mitochondrial OXPHOS and suggest that NNMT and DNMT1 are faithful biomarkers for OXPHOS‐targeting cancer therapies.